Subjective experience of personality dimensions in 1st degree relatives of schizophrenics - Maggini, C.; Raballo, A. (Acta Biomedica Atenei Parmensis, 2003)
An increasing number of studies suggest the usefulness of both personality features and neurocognitive vulnerability as tools for isolating phenotypes associated with susceptibility to schizophrenia, however the clinical and heuristic topicality of self-experienced vulnerability has yet to be properly recognized. Biological relatives of schizophrenic patients (because of the familial/genetic load) constitute a promising and suggestive paradigm for addressing the psychopathological relationship between personality features and subjective experience of vulnerability. The current study found that 1st degree unaffected relatives of schizophrenics exceeded normal controls in schizotypal, paranoid, and borderline dimensions, and showed an overlap in the schizoid dimension of clinical Schizotypals (i.e. Schizotypal Personality Disorder Patients). Subsequent correlation analysis showed that schizotypal and schizoid traits are linked to specific domains of self-experienced vulnerability. Clinical heuristics is discussed.